Role of Peoxisome Proliferator Activator Receptor 𝛾 on Blood Retinal Barrier Breakdown - Yasuo Yanagi (PPAR Research)
The retinal vessels have two barriers: the retinal pigment epithelium and the retinal vascular endothelium. Each barrier exhibits increased permeability under various pathological conditions. This condition is referred to as blood retinal barrier (BRB) breakdown. Clinically, the most frequently encountered condition causing BRB breakdown is diabetic retinopathy. In recent studies, inflammation has been linked to BRB breakdown and vascular leakage in diabetic retinopathy. Biological support for the role of inflammation in early diabetes is the adhesion of leukocytes to the retinal vasculature (leukostasis) observed in diabetic retinopathy. PPAR𝛾 is a member of a ligand-activated nuclear receptor superfamily and plays a critical role in a variety of biological processes, including adipogenesis, glucose metabolism, angiogenesis, and inflammation. There is now strong experimental evidence to support the theory that PPAR𝛾 inhibits diabetes-induced retinal leukostasis and leakage, playing an important role in the pathogenesis of diabetic retinopathy. Therapeutic targeting of PPAR𝛾 may be beneficial to diabetic retinopathy.